Astegopteryx spinocephala (Hemiptera: Aphididae), a new aphid species producing sterile soldiers that guard eggs laid in their gall - Kurosu U. (2014)
Astegopteryx spinocephala sp. nov., a soldier-producing aphid species forming banana-bunch shaped galls on Styrax benzoides in northern Thailand, is described. We found that galls of the species are formed in approximately June and last for almost 1 year, and that the aphid completes its life cycle without migrating to secondary hosts. Many alate sexuparae appeared in March/April, when many sexuals (arostrate males and rostrate females) and eggs were found in live subgalls guarded by soldiers that plugged the ostiole with their sclerotized, spiny heads. Two healthy galls sampled in April contained 2799 and 2659 eggs, respectively. Many live galls were still found in May, and some at the beginning of June. These galls contained both active soldiers and eggs, some of which had already hatched. This indicates that soldiers of A. spinocephala guard eggs until they hatch in at least some galls. ? 2006 The Entomological Society of Japan.